STRATEGI PENGEMBANGAN USAHA TAHU PADA INDUSTRI TAHU âVIVIâ DI KOTA PALU - Nurlina, Nurlina; Lamusa, Arifuddin (AGROTEKBIS, 2017)
Tofu Industry of "Vivi" is one of the industries that produce refined products with soy-based, location of industry Tofu "Vivi" is in Jl. Buah Pala No. 09, Village Boyaoge, Tatanga District of the city of Palu, Central Sulawesi. This study aims to determine the revenue earned by Industry of Tofu "Vivi" in producing tofu and to know the business development strategies in the industry of Tofu "Vivi", Results of the analysis showed that the income earned by industry of Tofu "Vivi" in January until the month of February amounted Rp. 32.318.058,-. Based on the analysis of studies using SWOT analysis It can be concluded that the position of business development strategies in the industry of Tofu "Vivi" is in quadrant I (one), This shows the position of the focused strategy for business development to Tofu "Vivi" is using S-O strategy is to use all our power to seize and exploit opportunities as possible Keywords: Business Development Strategy, Industrial Tofu "Vivi", Soy.